2020
DOI: 10.3390/en13133392
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Drying Temperature and Grinding Technique on Biomass Grindability

Abstract: The process of biomass compaction depends on many factors, related to material and process. One of the most important is the proper fragmentation of the raw material. In most cases, more fragmented raw material makes it easier to achieve the desired quality parameters of pellets or briquettes. While the chipping of biomass prefers moist materials, for grinding, the material needs to be dried. As drying temperature changes the properties of the material, these may affect the grinding process. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 88 publications
1
37
0
Order By: Relevance
“…These results indicate that, as is well known in the production of carbonized solid biofuels, in order to obtain the best process conditions of the torrefaction process and a reasonable price of the final product, it is important to achieve a mass loss on a level of 30% and an energy loss (torgas) on a level of 10% in the thermo-chemical conversion. Compared to research results on other energy crops and straw biomass, Jerusalem artichoke’s temperature of 245 °C during torrefaction for carbonized solid biofuel production under isothermal conditions is relatively low [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Research on the Jerusalem artichoke has shown that the amount of ash after the torrefaction process is still at a relatively low level compared to biomass not subjected to the torrefaction process (Jerusalem artichoke unprocessed as a result of the torrefaction process has an ash content of <3%), and solid fossil fuels, such as Polish hard coal, have an ash content of <15%.…”
Section: Discussionmentioning
confidence: 94%
“…These results indicate that, as is well known in the production of carbonized solid biofuels, in order to obtain the best process conditions of the torrefaction process and a reasonable price of the final product, it is important to achieve a mass loss on a level of 30% and an energy loss (torgas) on a level of 10% in the thermo-chemical conversion. Compared to research results on other energy crops and straw biomass, Jerusalem artichoke’s temperature of 245 °C during torrefaction for carbonized solid biofuel production under isothermal conditions is relatively low [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Research on the Jerusalem artichoke has shown that the amount of ash after the torrefaction process is still at a relatively low level compared to biomass not subjected to the torrefaction process (Jerusalem artichoke unprocessed as a result of the torrefaction process has an ash content of <3%), and solid fossil fuels, such as Polish hard coal, have an ash content of <15%.…”
Section: Discussionmentioning
confidence: 94%
“…49% on the dry basis [ 56 , 57 ], which makes BSG not significantly different in terms of its fuel properties, in comparison to lignocellulosic biomass. Additionally, ash content varies between 2 and 6% [ 57 , 58 , 59 ], which is similar to different types of agricultural biomass [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. However, high moisture content, exceeding 70% [ 56 , 57 ], is a significant obstacle in the use of BSG as a solid biofuel.…”
Section: Thermal Valorization Of Bsgmentioning
confidence: 99%
“…In the case of torrefaction, this effect is undeniable and improves the conversion by increasing the brittleness of the material [ 46 , 65 ]. A lower temperature range (60–140 °C) [ 22 , 66 ] also affects the grindability of the raw material, which makes it possible to obtain material of a finer grain size with the same, or even lower, input. Moreover, higher brittleness of such material will also be a factor influencing reduction of SP.…”
Section: Resultsmentioning
confidence: 99%
“…Process parameters include agglomeration pressure, temperature, and geometry of the matrix channel or compression chamber. Material parameters are type of biomass, moisture content, degree of fragmentation, and method of raw material preparation (e.g., drying the material) [ 20 , 21 , 22 ]. The main quality parameters depending on process and material factors are mechanical durability (DU) and specific density.…”
Section: Introductionmentioning
confidence: 99%